Analisis Efisiensi Bank Aceh Syariah di Kota Aceh Tenggara dengan Stochastic Frontier Approach (SFA) - Sheila Anggraini; Tuti Anggraini (ITB AAS INDONESIA Surakarta, 2023)
This study measures the efficiency of Islamic banks using the Stochastic Frontier Approach (SFA) method. This method has advantages over other measurement methods. According to Coelli et al in Hakim (2009), the advantage of SFA compared to other models is first, the involvement of disturbance terms that represent interference, measurement errors, and exogenous shocks that are out of control. Second, environmental variables are easier to treat, allow hypothesis testing using statistics, and easier in identifying outliers. In this study, input variables and output variables were determined based on an intermediation approach by considering the main function of banks as financial intermediation, with measurements using the frontier production function. The results of calculating the level of efficiency using the SFA method with the production function show that BAS always experiences an increase in efficiency every year with an average BAS efficiency level slightly higher, namely 0.9516 than BUS which has an average efficiency level of 0.9467. This shows that during 2019-2022 BAS is slightly more optimal in producing total credit output from existing inputs. BAS efficiency which is in the range of efficiency level 0.9 shows that during the 2019-2022 period it has reached the level of efficiency even though it has not reached the level of full efficiency or efficiency with a value of 1.